Identifikasi Tenaga Kerja Sektor Manufaktur Dan Tenaga Kerja Total Kabupaten/Kota Kawasan Investasi di Indonesia Timur - M. Firmansyah (EKO-REGIONAL, 2006)
This article identify the area or location where the higher owning labors concentration of manufactures and the total of labors in Investment area of the East Indonesia, also how deep influence of regional income, mean wage rate and HDI (Human Development Index) to the labors concentration. It uses Klasem typology and linear regression analysis by using cross sectional data on 2000.The results that the most regions in the area of East Indonesia keep have low of concentration labors. Higher areas on labors concentration are still predominated by Kalimantan and Sulawesi, while lower of labors concentration will reside in NTT and Papua.Statistically regions income have an effect in improving labors concentration, that indicate higher income is enable to the region which are opening a new enterprises on the area. The other conclusion that industry manufactures are more interest to choose on location which are lower wage. Related to the human resource, labors concentration location totally is dominated by low resident of human resource in the area.Key word: Labors Concentration, Typology, Investment Area, East Indonesia.